RECONSIDERING BETWEEN REASON AND REVELATION IN ISLAMIC LEGAL PHILOSOPHY - Muhammad Hidayat (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This research aims to discuss reason and revelation in the context of Islamic Legal Philosophy, with a focus on their respective roles in the law-making process. Exploring how these two elements interact in the determination of Islamic law. The formulation of the problem raised is how reason and revelation complement each other in forming a relevant and dynamic legal basis. The research method used is a literature review with a descriptive-analytical approach, which involves text analysis of scientific publications and works relevant to the study theme. The research results show that revelation holds the highest authority as a source of law, while reason functions as a methodological tool for understanding and applying revelation in changing contexts. Even though reason has limitations, its role is very important because revelation must always be related to benefit as the main goal of Islamic law. Supervision of the use of reason is necessary to ensure conformity with the principles of revelation. This research confirms that reason and revelation in Islamic Legal Philosophy have a mutually reinforcing relationship, and the two cannot be separated. The power of reason in understanding revelation ensures the relevance of Islamic law to changing times.